Effects of fertigation with raw sewage on the vegetative development of maize and beans - Matheus Oliveira; Juliano Siqueira; Mateus Matos; Luciene Siniscalchi; Willian Fim (International Journal of Recycling of Organic Waste in Agriculture, 2022)
Purpose Fertigation plays an important role in the so-called circular economy since it relies on the reuse of water and nutrients; therefore, this method is fundamental for production in areas with scarce resources. This study aimed to evaluate the effects of fertigation of soil plots with sewage on soil attributes, germination of seeds, and growth of bean and corn.Method Due to the low concentrations of macronutrients in the sewage, the applied dose was calculated based on the water deficit. Three plots cultivated with maize and three plots cultivated with beans were fertigated, while the same number of plots received irrigation and mineral fertilization in amounts equivalent to the dose of nitrogen administered in the sewage for comparison.Results There was an increase in the cation exchange capacity (74.6%), nitrogen (10.4%), available phosphorus (190.5%), and organic matter (44.9%) contents in the fertigated soil compared to those in the soil of the plots that received chemical fertilization, resulting in greater germination and corn and bean growth. Analyses indicated that the coliform count in beans is below the detection limit of the technique used.Conclusion Based on the results obtained, there are indications that fertigation can provide improvements in soil attributes at values higher than those provided by chemical fertilization, reducing the need to apply these macronutrients and irrigation water to the soil. Furthermore, fertigation can be sanitary and safe, since the count of microorganisms in the beans was not higher than that recommended by the World Health Organization (WHO).